A Shopping Aid Device for the Visually Impaired Using Arduino Mega and Barcode Module - RAMBE, MUHAMMAD ANUGRA RIZKY; Salryanto, Hurin Syatta Fikri Murda; Annisa Andriyana; Pabilang, Mutiara Sony (Universitas Telkom, 2024)
Over the past five years, the number of blind and visually impaired (BVI) individuals in Indonesia has reached approximately 3.6 million in 2023. Based on interviews with Indonesian Union for the Visually Impaired (PERTUNI), it was found that blind and visually impaired (BVI) individuals often face limited independence, leading to reduced self confidence. A common challenge is daily grocery shopping, where they frequently require companions, and the absence of such support makes it difficult to ensure that the selected products are correct. PERTUNI also highlighted that assistive devices for this kind of problem are rarely developed, despite being urgently needed by almost all BVI individuals. To address this gap, we developed Drishti, a compact and portableassistive system specifically designed to support shopping activities by detecting product names through barcode recognition and providing audio feedback. Unlike most existing assistive devices that rely on camera based systems, Drishti employs a dedicated barcode sensor. In addition, the system is designed to be lightweight and operating without internet connectivity, ensuring usability anytime and anywhere. Drishti also functions as a validator, aiming to enhance the confidence and comfort of BVI individual during shopping. The prototype demonstrated a 67% accuracy rate in detecting products with EAN type barcodes under various lighting conditions and product states, while maintaining clear audio feedback across all trials. These results position Drishti as a promising prototype that can be further developed to enhance the shopping independence of BVI individuals